Effects of using live grass shrimp (Palaemonetes varians) as the only source of food for the culture of cuttlefish, Sepia officinalis (Linnaeus, 1758) - Sykes, António V. (2018)
The life cycle of cuttlefish fed ad libitum exclusively on live grass shrimp (Palaemonetes varians) was studied during 5 consecutive generations. Different culture temperatures promoted different (P < 0.05) exponential growth for each life cycle, being summer generations shorter than those of winter. Higher temperatures promoted higher IGR’s and mortality, while lower temperatures promoted increased life span, reproduction stages, total fecundity and total egg biomass. Increased generations also seemed to increase fertility. A ‘‘hybrid’’ generation promoted the best results in terms of hatchling weight, individual fecundity and fertility. Mean egg weight was related to female size and embryonic development took longer at lower temperatures. Brood stock sex ratios seemed to be temperature related.All of these culture aspects were also compared between themselves in order to establish future brood stock methodologies. Grass shrimp proved to be a good diet for the culture of cuttlefish throughout the life cycle. The use of only one species reduces costs and labor associated to cuttlefish culture.